2022
DOI: 10.3389/fgene.2022.957744
|View full text |Cite
|
Sign up to set email alerts
|

A novel cuproptosis-related gene signature for predicting prognosis in cervical cancer

Abstract: Purpose: Cuproptosis, a form of copper-induced cell death, can be a promising therapeutic target for refractory cancers. Hence, we conducted this research to explore the association between cuproptosis and prognosis in cervical cancer (CC).Methods: For constructing a prognostic signature based on cuproptosis-related genes from TCGA database, the least absolute shrinkage and selection operator Cox regression was utilized. The GSE44001 cohort was utilized for validation.Results: A total of nine cuproptosis-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Abnormal accumulation of intracellular copper induces a new mode of cell death, copper drooping ( Kahlson and Dixon, 2022 ). The copper homeostasis has been associated with the development and prognosis of patients with various tumors ( Feng et al, 2022 ; Huang et al, 2022 ; Lei et al, 2022 ; Li et al, 2022 ; Wang et al, 2022 ). As a copper death-related gene, LIPT1 is required for lipoylation and activation of 2-ketoacid dehydrogenases in humans ( Tort et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal accumulation of intracellular copper induces a new mode of cell death, copper drooping ( Kahlson and Dixon, 2022 ). The copper homeostasis has been associated with the development and prognosis of patients with various tumors ( Feng et al, 2022 ; Huang et al, 2022 ; Lei et al, 2022 ; Li et al, 2022 ; Wang et al, 2022 ). As a copper death-related gene, LIPT1 is required for lipoylation and activation of 2-ketoacid dehydrogenases in humans ( Tort et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, researchers have recently started focusing on the relationship between cuproptosis and several cancers, and constructed some different cuproptosis‐related gene signatures for predicting prognosis in cervical cancer, 29 pancreatic cancer, 30 Clear Cell Renal Cell Carcinoma 31 . LncRNAs are potential biomarkers that can be used to treat numerous diseases, especially tumors 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the oxidative phosphorylation inhibitor Gboxin analog was found to have a strong proliferation inhibitory and cell cycle blocking effect on DLBCL with specific selectivity for it ( 34 ). Several recent studies have revealed the potential role of CRGs in the prognosis of cancers, such as kidney cancer ( 35 42 ), hepatocellular carcinoma ( 43 47 ), lung cancer ( 48 53 ), head and neck squamous cell carcinoma ( 53 60 ), glioma ( 61 66 ), breast cancer ( 67 70 ), endometrial carcinoma ( 71 , 72 ), melanoma ( 73 75 ), pancreatic cancer ( 76 , 77 ), colorectal cancer ( 78 81 ) and so on. However, no reports describe any effects of the cuproptosis regulatory mechanism on DLBCL.…”
Section: Introductionmentioning
confidence: 99%